2020
DOI: 10.3390/e22030342
|View full text |Cite
|
Sign up to set email alerts
|

Land-Cover Classification Using MaxEnt: Can We Trust in Model Quality Metrics for Estimating Classification Accuracy?

Abstract: MaxEnt is a popular maximum entropy-based algorithm originally developed for modelling species distribution, but increasingly used for land-cover classification. In this article, we used MaxEnt as a single-class land-cover classification and explored if recommended procedures for generating high-quality species distribution models also apply for generating high-accuracy land-cover classification. We used remote sensing imagery and randomly selected ground-true points for four types of land covers (built, grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The accuracy metric considers the values of true positives and true negatives while the F1-score [ 76 ] helps to make crucial facts that arise due to the values of false negatives and false positives. Since, the F1-score is the harmonic mean of recall and precision, it gives a better idea about the incorrectly classified cases.…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy metric considers the values of true positives and true negatives while the F1-score [ 76 ] helps to make crucial facts that arise due to the values of false negatives and false positives. Since, the F1-score is the harmonic mean of recall and precision, it gives a better idea about the incorrectly classified cases.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review confirmed that thresholding is the parameter that influences the accuracy of OCCs the most [42,73] and that a threshold remains challenging to set [51,53]. Although Chignell et al [46] noted that a continuous map is more informative than a categorized map for end-users, few of the studies reviewed avoided thresholding (Table 8).…”
Section: Thresholdingmentioning
confidence: 97%
“…Although Sentinel-1 and Sentinel-2 data have been freely available since 2014 and 2016, respectively, their use for mapping vegetation in OCCs remains low (n = 6). Indeed, most studies used multi temporal Sentinel-2 images [45,[71][72][73][74] whereas one study used Sentinel-1 images [75].…”
Section: The Importance Of Spatio-temporal Resolutionsmentioning
confidence: 99%
See 2 more Smart Citations